Design and experimental research on the sweet potato seedling transplanting mechanism of the planetary gear train with deformed elliptical gear transmission - Ye, Bingliang; Ye, Yuxuan; Zhou, Haili; Yu, Gaohong; Zhao, Xiong; Deng, Bin (International Journal of Agricultural and Biological Engineering, 2024)
Aiming at the lack of suitable machines for sweet potato seedling transplanting in China, and according to the agronomic requirements for the horizontal insertion method of sweet potato seedling, a new sweet potato seedling transplanting mechanism of planetary gear train was proposed based on the non-uniform transmission of deformed elliptical gear. The working principle of the transplanting mechanism was analyzed, and the kinematics modeling and analysis of the mechanism were carried out. The study established the numerical objectives of the transplanting mechanism and applied the theory of membership function to establish a mathematical model for the parameter-guided optimization design of the transplanting mechanism. The parameter-guided optimization design software was developed to obtain a set of optimal mechanism parameters that satisfied the motion trajectory of sweet potato transplanting and the posture of the transplanting arm. Based on the optimized parameters, the structure of the transplanting mechanism was designed, and a virtual prototype of the mechanism was created, whereby a virtual motion simulation of the transplanting mechanism was conducted to verify the correctness of the kinematics model and design of the mechanism. The high-speed photographic kinematics test of the mechanism prototype and sweet potato seedling transplanting tests were conducted to test the mechanism’s kinematic characteristics and transplanting performance. The test results show that the test trajectory of the mechanism and test posture of the transplanting arm are almost consistent with the theoretical and simulation trajectory, meeting the agronomic requirements of the horizontal insertion method of sweet potato seedling; And when the rotary speed of the mechanism are 20 r/min and 30 r/min, the average success ratios of sweet potato seedlings transplanting are 90% and 82%, respectively, which prove the application feasibility of the mechanism in the practical machines. Keywords: sweet potato seedling transplanter, transplanting mechanism, deformed elliptical gear transmission, kinematics analysis, membership function, optimization design DOI: 10.25165/j.ijabe.20241703.8543 Citation: Ye B L, Ye Y X, Zhou H L, Yu G H, Zhao X, Deng B. Design and experimental research on the sweet potato seedling transplanting mechanism of the planetary gear train with deformed elliptical gear transmission. Int J Agric & Biol Eng, 2024; 17(3): 91-99.